Calibration of a novel microstructural damage model for wire bonds - Yang, L.; Agyakwa, P.A.; Johnson, C.M. (Institute of Electrical and Electronics Engineers, 2014)
In a previous paper, a new time-domain damage-based physics model was proposed for the lifetime prediction of wire bond interconnects in power electronic modules. Unlike cycle-dependent life prediction methodologies, this model innovatively incorporates temperature- and time-dependent properties so that rate-sensitive processes associated with the bond degradation can be accurately represented. This paper presents the work on the development and calibration of the damage model by linking its core parameter, i.e., “damage,” to the strain energy density, which is a physically quantifiable materials property. Isothermal uniaxial tensile data for unbonded pure aluminum wires (99.999%) have been used to develop constitutive functions, and the model has been calibrated by the derived values of the strain energy density.